Impact Investing in Africa A Guide to Sustainability for Investors, Institutions, and Entrepreneurs - Mungai, Edward (Springer International Publishing, 2018)
As investment in new ventures across the African continent grows, and enterprises multiply in a wide variety of sectors, the next wave of challenges and opportunities has become apparent to those with the experience and vision to understand them. In this book for investors, institutions, entrepreneurs, and everyone interested in the economic future of Africa, noted Kenyan executive Edward Mungai will analyze recent successes and failures in business ventures across the African continent and identify the most important opportunities for impact investment impacting the future of Africa available today and in the near future.